Construcionismo social, saúde mental e clínica psicológica na obra de Kenneth Gergen - Rodrigues, Clara Mória Borges (2023)
This dissertation addresses aspects of Kenneth Gergen's work with regard to the approximation of his studies on mental health and clinical psychology. Kenneth Gergen is the pioneer of the discussion on Social Constructionism, being a reference in the subject. The affinity of the discussion is related to the non-pathologizing and de-individualizing proposals of clinical work, favoring the co-construction of meaning, relational processes, and humanizing practices. The investigation on aspects of mental and clinical health based on Gergen's studies in this dissertation is organized into two distinct theoretical essays: the first discusses the deficit discourse and the social construction of psychopathology; and the second deals with the conception of clinic, therapy and therapeutic change. The first study revealed a critique of traditional psychopathologizing models in the clinic, emphasizing the cultural consequences of language uses that highlight the deficit. The second study maps Gergen's considerations on clinical practice, therapy and social change, focusing on the notion of therapy as a social construction. Such studies are intersected and initiated for scientific production in the field of Psychology and Social Constructionism by proposing reflections on clinical practice and on the paths we have followed, as a community of professionals in the field of mental health.